Correlation between oropharyngeal pH‐monitoring and esophageal pH‐impedance monitoring in patients with suspected GERD‐related extra‐esophageal symptoms. Issue 11 (10th September 2014) - Mazzoleni, G.; Vailati, C.; Lisma, D. G.; Testoni, P. A.; Passaretti, S.
Abstract Background 24‐hour esophageal pH‐impedance (pH‐MII) is not totally reliable for laryngopharyngeal reflux (LPR). Oropharyngeal (OP) pH‐monitoring with the Dx‐pH probe may detect LPR better. The correlation between these two techniques is not thoroughly established. Aim of this study is to examine the correlation between OP pH‐metry and esophageal pH‐MII monitoring. Methods Thirty‐six consecutive patients with suspected gastroesophageal reflux disease‐related extra‐esophageal symptoms were evaluated using 24‐h OP‐pH and concomitant esophageal pH‐MII monitoring. OP events were defined as: drop in pH below thresholds of 5.5, 5.0, 4.5, 4.0 or drop in pH of at least 10% from a running baseline. Temporal relationship between OP and esophageal reflux events and outcomes of the two tests were evaluated. Key Results 2394 refluxes were detected by pH‐MII; of these only 120 were detected also by OP Dx‐probe. On the other hand, the proportion of OP‐pH events which were temporally related to an episode of distal reflux ranged from 0% to 17%, depending on the proximal pH criteria used. In 8/36 patients both tests were pathological, while in 10/36 they were both normal; 14/36 patients had pathological OP reflux, but a normal pH‐MII test; 4/36 patients had pathological pH‐MII, but a normal OP reflux. Conclusions & Inferences The correlation between OP pH‐metry and pH‐MII was weak. At present, the absence of a reliable gold standard for the diagnosis of LPR and the uncertain etiology of the pharyngeal pH alterations make it difficult to decide which is the most reliable technique for the diagnosis of true LPR.